Effect of cure cycles on residual stresses in thick composites using multi-physics coupled analysis with multiple constitutive models. (August 2022) - Wang, Qi; Yang, Xufeng; Zhang, Xiaowen; Chang, Xin; Yap, Malvern; Chen, Zhong; Ren, Mingfa
Abstract: This paper deals with the influence of cure cycles on residual stresses, degree of cure (DOC), and process time based on the fully coupled thermomechanical analysis. The viscoelastic, cure-hardening-instantaneously-linear-elastic, and path-dependent constitutive models are implemented and compared by finite element analyses. The analytical sensitivity analysis which makes full use of the physical insight is conducted utilizing the radial basis function surrogate technique to obtain the visualized relationships between the cure cycle parameters and the target variables. Subsequently, the optimizations of cure cycles with and without the viscoelastic analysis are conducted. The results indicate that the temperature and duration of the second dwell have the greatest effect on the residual stresses. Minimizing DOC results in similar results in minimizing residual stresses when design variables only involve the dwell temperatures and the duration time. However, full parameters optimization which considers the stress relaxation is necessary to achieve the best cure cycle design. Graphical Abstract: ga1